2004
DOI: 10.1111/j.0306-686x.2004.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Market Valuation of Successful versus Non‐successful R&D Efforts in the Pharmaceutical Industry

Abstract: This paper examines the relationship between a non-financial measure of successful research and development (R&D) efforts in the pharmaceutical industry and R&D expenditures. I hypothesize that the R&D of successful producers will be valued more by the market than the R&D of non-successful producers. The regression results support the hypothesis. In the primary model, R&D is not associated with price; however, the coefficient on the interaction between R&D and successful developers is positively related to sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 17 publications
2
24
0
3
Order By: Relevance
“…A number of studies find that the capital market prices R&D expenditures as an intangible asset (Hirschey and Weygandt, 1985;Sougiannis, 1994;Lev and Sougiannis, 1996;Shortridge, 2004). Furthermore, Chan et al (2001) provide evidence that, on average, the market fully incorporates the benefits of R&D expenditures.…”
Section: Related Literaturementioning
confidence: 99%
“…A number of studies find that the capital market prices R&D expenditures as an intangible asset (Hirschey and Weygandt, 1985;Sougiannis, 1994;Lev and Sougiannis, 1996;Shortridge, 2004). Furthermore, Chan et al (2001) provide evidence that, on average, the market fully incorporates the benefits of R&D expenditures.…”
Section: Related Literaturementioning
confidence: 99%
“…[14] Others have found that financial market losses from product development failures are larger in magnitude than gains from successes. [15], [16] There has been limited empirical work examining how and to what extent the stock market values measures of R&D, such as clinical trials, for investigational compounds. A pair of studies, one on oncology drugs [17] and another on biotechnology products [18], found that there are measurable changes in company stock prices before important trial announcements and significant differences in stock price changes between companies with a successful product versus those with an unsuccessful product.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, US firms' foreign pharmaceutical R&D grew from only $US2.8 billion in 1999 to $US3.2 billion in 2002. 12 The R&D data are not broken down by country, but the Bureau of Economic Analysis [24,25] reports that European nations accounted for between 80% and 90% of it.…”
Section: Us-eu Randd Growth Differencesmentioning
confidence: 99%
“…[8][9][10][11] There are strong links between successful pharmaceutical firms' R&D spending and their stock prices. [12] 1. EU and US Pharmaceutical Prices EU pharmaceutical price regulations take various forms, and many countries use more than one.…”
mentioning
confidence: 99%